Hepatoprotektif Ekstrak Batang Bajakah (Spatholobus littoralis Hassk) Induksi Tetraclorida (CCL4) - Mustika Sari; Nawawi Nawawi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to explore the benefits of bajakah (Spatholobus littoralis Hassk) through the study of its utilization as a hepatoprotector. This research method is quantitative. Bajakah stem extract was made using 96% ethanol solvent using the maceration method. Analysis was carried out using liver histology preparations to determine the HAI (Histology Activity Index) Knodel Score. The treatment group consisted of 5 groups, namely, a) negative control (K1) treated with toxic doses of CCL4; b) positive control, namely vitamin E 46.8 mg/KgBW; c) P1 (treatment 1) was 750 mg/KgBW of Bajakah stem extract; d) P2 (treatment two) was 1200 mg/KgBW of pirated stem extract; e) P3 (treatment of three) was extract of the stem of Bajakah 1500 mg/KgBB. The results showed that the post hoc LSD test results in the P1 group had a histopathological picture of damaged liver, there was a significant difference with the K and P3 groups (p <0.05), but there was no significant difference when compared with the P2 group. Meanwhile, the P3 group had significant differences when compared to all groups (p <0.05). In conclusion, the administration of extract of pirated stems at a dose of 1,500 mg/Kg has a significant effect on the HAI value on the average number of hepatocytes with parenchymatous degeneration and necrosis after CCL4 induced Keywords: Bajakah, CCL4, Hepatoprotective